2014
DOI: 10.1103/physrevlett.112.128302
|View full text |Cite
|
Sign up to set email alerts
|

Chaotic Induced-Charge Electro-Osmosis

Abstract: We present direct numerical simulations of the coupled Poisson-Nernst-Planck and Navier-Stokes equations for an electrolyte around a polarizable cylinder subject to an external electric field. For high fields, a novel chaotic flow phenomenon is discovered. Our calculations indicate significant improvement in the prediction of the mean flow relative to standard asymptotic models. These results open possibilities for chaos-enhanced mixing in microdevices and provide insight into barriers to efficient electrokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
83
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(90 citation statements)
references
References 26 publications
6
83
0
Order By: Relevance
“…A number of different mechanisms have been suggested as explanation for this overlimiting current, most of which are probably important for some system configuration or another. The suggested mechanisms include bulk conduction through the extended space-charge region [4,5], current induced membrane discharge [6], water-splitting effects [7,8], electroosmotic instability [9,10], and most recently, electro-hydrodynamic chaos [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…A number of different mechanisms have been suggested as explanation for this overlimiting current, most of which are probably important for some system configuration or another. The suggested mechanisms include bulk conduction through the extended space-charge region [4,5], current induced membrane discharge [6], water-splitting effects [7,8], electroosmotic instability [9,10], and most recently, electro-hydrodynamic chaos [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Second, we do observe a fieldinduced redistribution of ions, Fig.2. However, the velocity reduction factor cp  caused by concentration polarization has been predicted to be only about 5 [17], thus the effect is unlikely to be the sole factor responsible for the smallness of velocities. Among other reasons are surface contamination [23] and roughness [24], interactions with walls [13], confinement-enhanced viscous friction [25] and the assumption of small voltages Metal-dielectric Janus spheres produce dipolar flows and pumping effects, with contributions ~cos , ~sin to the radial and azimuthal components of ICEO velocities, respectively.…”
mentioning
confidence: 99%
“…Even for the simple case of a homogeneous metallic sphere, it is unclear why the experimental velocities [10,13] Recent numerical simulations [17] suggest that one of the reasons might be the concentration polarization effect [18][19]. , since it has been reported that pure water yields the highest electrophoretic velocity of Janus particles while addition of salts cause a slow-down [13].…”
mentioning
confidence: 99%
“…41 The thin layer approximation simplifies the theoretical analysis of AC-FFET induced particle concentrating by assuming the liquid bulk electroneutral, since the induced free charge merely exists within a small region at the electrode/liquid interface. [42][43][44][45][46][47] In this work, we extended the previous theoretical analysis in Ref. 48 and computed FIG.…”
Section: Introductionmentioning
confidence: 70%